Strategi Diversifikasi dan Kinerja Perbankan: Good Corporate Governance sebagai Pemoderasi - Nathania Sandra; Dyna Rachmawati (Jurnal Ekonomi Akuntansi dan Manajemen, 2023)
This study aims to examine first, the application of diversification strategy to banking performance. The banking industry has not been studied much in previous studies. The banking industry is an industry that is highly regulated by the government or highly regulated. This resulted in the intensity of competition in this industry. Diversification can be one way to overcome the threats faced by banks. The bank diversification strategy in this study is divided into 2 segments, namely: banking products and banking operational areas. The implementation of a diversification strategy in banking has resulted in more diverse management duties and responsibilities in controlling their subordinates, thus requiring good corporate governance (GCG). GCG is expected to support the effectiveness of diversification strategy implementation. The second objective of this study is to examine the role of GCG as a moderator in the relationship between the diversification strategies on banking performance. This study uses 150 banking objects listed on the Indonesia Stock Exchange for the 2016-2020 periods. The results of this study prove that, first, the strategy of diversifying the operational area (product) segment is able to increase (decrease) banking performance. Second, GCG has a moderating role. GCG in diversifying the operational area (product) segment strengthens (weakens) its positive (negative) impact on banking performance. The results of this study have implications, namely (1) banking management needs to implement a diversification strategy to improve its performance, and (2) GCG is important for banks because it is able to support the effectiveness of diversification strategies. Keywords: Diversification Strategy, Bank Performance, Good Corporate Governance